Implementasi Manajemen Sumber Daya Manusia di Pusat Informasi dan Konseling Remaja (PIK-R) Bangka Jakarta Selatan Provinsi DKI Jakarta - Arya Saputra Ramadani; Ananda Stevvan Vallentino Petrix Pratama (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The Youth Information and Counseling Center (PIK-R) serves as a strategic platform aimed at supporting adolescents in developing their capacity through information, education, and counseling. This study aims to analyze the implementation of human resource management (HRM) at PIK-R Bangka, DKI Jakarta, recognized as one of the Best National Model PIK-R in the Collaborative Age Category (20-24 age) 2024. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings reveal that HRM at PIK-R Bangka encompasses five main aspects: (1) member recruitment is conducted openly and transparently to attract talented adolescents with strong commitment; (2) member selection involves administrative processes, interviews, and simulations to ensure candidates meet organizational needs; (3) training and capacity development are routinely implemented to enhance members' technical and non-technical competencies; (4) performance evaluation employs measurable indicators such as attendance, program participation, and beneficiary feedback; and (5) quality improvement strategies include rewards, self-development programs, and collaboration with local to international communities. This study highlights that effective HRM implementation significantly contributes to PIK-R Bangka's success in achieving organizational objectives.